2021
DOI: 10.5194/jsss-10-153-2021
|View full text |Cite
|
Sign up to set email alerts
|

An internet of things (IoT)-based optimum tea fermentation detection model using convolutional neural networks (CNNs) and majority voting techniques

Abstract: Abstract. Tea (Camellia sinensis) is one of the most consumed drinks across the world. Based on processing techniques, there are more than 15 000 categories of tea, but the main categories include yellow tea, Oolong tea, Illex tea, black tea, matcha tea, green tea, and sencha tea, among others. Black tea is the most popular among the categories worldwide. During black tea processing, the following stages occur: plucking, withering, cutting, tearing, curling, fermentation, drying, and sorting. Although all thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The results show that LeafNet was superior in the recognition of tea leaf diseases compared to the MLP and SVM algorithms. Kimutai et al [28] proposed a deep learning model named TeaNet to detect the optimum fermentation of tea. The experimental results showed that TeaNet was superior in the classification tasks compared to the other machine learning techniques, including KNN, SVM, RF, and linear discriminant analysis (LDA).…”
Section: Image-based Tea Quality Identificationmentioning
confidence: 99%
“…The results show that LeafNet was superior in the recognition of tea leaf diseases compared to the MLP and SVM algorithms. Kimutai et al [28] proposed a deep learning model named TeaNet to detect the optimum fermentation of tea. The experimental results showed that TeaNet was superior in the classification tasks compared to the other machine learning techniques, including KNN, SVM, RF, and linear discriminant analysis (LDA).…”
Section: Image-based Tea Quality Identificationmentioning
confidence: 99%
“…Many researchers have applied IoT in the food fermentation process to enhance high‐nutritional content and process optimization. Kimutai et al (2021) investigated how IoT, deep convolutional neural networks (CNN), and image processing may be used with majority voting strategies to choose the best black tea fermentation process. To picture tea in real‐time while the fermentation process developed, the authors built a prototype utilizing Raspberry Pi 3 models and a Pi camera.…”
Section: Survey Of Iot Architecture and Iot Application In Food Ferme...mentioning
confidence: 99%
“…IoT innovation has found a wide variety of uses ranging from development to designing, medication, fabricating, sports, and administration to practically all sectors of the economy (Kimutai et al, 2021). In addition, IoT has recently found a significant application in the agricultural sector.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation